2021
DOI: 10.1111/ijfs.15167
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions of insect consumption: a review of western research since 2015

Abstract: Edible insects have been touted as a sustainable food of the future, but for Western consumers, the concept of entomophagy is largely unfamiliar and often disgusting. This review article discusses current trends in perceptual entomophagy research in Australia, Canada, Europe and the USA since 2015, along with an analysis of the guiding theoretical approaches to predicting insect consumption. Instead of trying to convince unwilling consumers, sensory and consumer science should turn to optimising insect-eating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 104 publications
2
73
0
3
Order By: Relevance
“…All participants were informed of any allergens present in the test samples. Subsequently, subjects agreed with and signed a consent form included in the research protocol approved (IRB # HE 18-9 and # HE [18][19][20][21][22] by the LSU Agricultural Center Institutional Review Board.…”
Section: Subjectsmentioning
confidence: 99%
“…All participants were informed of any allergens present in the test samples. Subsequently, subjects agreed with and signed a consent form included in the research protocol approved (IRB # HE 18-9 and # HE [18][19][20][21][22] by the LSU Agricultural Center Institutional Review Board.…”
Section: Subjectsmentioning
confidence: 99%
“…The research protocol was approved by Louisiana State University (LSU) Agricultural Center Institutional Review Board (IRB # HE 18-9 and # HE [18][19][20][21][22]. Participants (n = 210 untrained consumers 18 years of age and older; Table 1) were recruited from a pool of faculty, staff, and students at the LSU campus, Baton Rouge, LA, USA.…”
Section: Consumer Studymentioning
confidence: 99%
“…Food neophobia is mainly related to unfamiliarity with novel foods while disgust is thought to be originated from mental associations with other disgusting variables, which makes it more complex to be understood and overcome or counterbalance. Both negative-product-elicited traits are considered the major limitation for the willingness to try edible insects in Western societies [21,49,50] although La Barbera et al [22] found them uncorrelated and determined that "disgusting" feelings were more important than neophobia when predicting the willingness to eat insects. Although ECP+ disclosed information communicated environmental and nutritional benefits associated with anthropo-entomophagy, the negative feelings and expectations exerted a stronger effect than the environmental or nutritional consciousness and positive sensations.…”
Section: Effects Of Formulation Disclosed Information and Gender On Expected And Actual Overall Likingmentioning
confidence: 99%
See 2 more Smart Citations